(untitled) (Revista cientifica In Vestigium Ire, 2020)
The exigencies and constant changes in the modern world are not foreign to the education sector which is expected to be in tune with the new realities, and for this, it is fundamental that innovative strategies be adopted in the processes of teaching and learning, including adjustments in methodology, resources and attitudes of both teachers and students. One of these actions is coaching, a management tool that aims to improve the performance of people, through a process of accompaniment and whose foundations can be incorporated into education. The article proposes that it is necessary to extrapolate coaching from the company to the classroom, which helps to create conditions for learning and develop the full potential of the student, making it the protagonist of their learning. The objective was centered in proposing coaching guidelines that can be applied by the teacher in his or her work; with the purpose of involving the students in a more participative way. In this perspective, a qualitative study was developed, by means of documentary research, on the elements that support educational coaching; the data analyzed allowed to recognize how the teaching function is enriched with the incorporation of coaching elements.